ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH PENDUDUK MISKIN DI KABUPATEN DAN KOTA PROVINSI BANTEN - Rizka Annisa; Hady Sutjipto (Tirtayasa Ekonomika, 2017)
Poverty has become a problem that always happens in the district Banten Province. In the last 6 years, in 2010 to 2015 the population of the poor in this province decline and a significants increase of large. In year 2015 the number of poor in the province of Banten experienced a significant increase of large, although in 2014 had improved. In reducing the number of poor people cannot be separated from issues such as the number of unemployment, GDRPper capita and the level of education that is a very influential. This research aims to understand how big variable influence te number of unemployment, per capita gross, and the level of education on the number of poor people in the districts province of Banten year 2010-2015 who later expected to be material considerations in determining a poverty reduction policies in the districts Banten Province. The data used is taken from secondary data from the statistic Banten. This study using methods panel data with  a fem model.The result of research showed that the variable the number of unemployment, and gdp per capita had a positive impact significant, a variable level of education have a negative influence significant impact on the number of poor people in the district Banten years of 2010 to 2015.